Evaluation of host humoral antibody production against Plasmodium falciparum recombinant circumsporozoite antigen in Nigerian children (2012)
Background & objectives: The challenge of malaria and efforts targeted at developing malaria vaccines triggered this study on the reactivity of IgG and its subclasses in the test serum specific to CSP. This work was directed at assessing the influence of age and gender on host humoral antibody against Plasmodium falciparum recombinant circumsporozoite antigen in Nigerian children. Methods: In all, 67 serum samples (>10,000 parasites/μl of blood) collected from malaria-infected children at the University College Hospital, Ibadan during the transmission season were analyzed by ELISA. Results: The mean absorbance values of IgG subclasses reactive against P. falciparum CSP appeared to be age dependent and ranged from 0.01 for IgG4 in younger children to 0.95 for IgG3 in older children. The sixty-seven subjects investigated in this study had significantly higher mean IgG1 and IgG3 than the uninfected controls (p <0.01). This follows the order IgG3 >IgG1>IgG2>IgG4 which confirmed the prevalence of the cytophilic antibodies (IgG1 and IgG3) in 65% of the malaria infected children over the non-cytophilic subclasses (IgG2 and IgG4). Similarly, there was low production of IgG4 and IgG2 levels in 35% of the subjects compared with control. IgG was detected in the serum of North American Subjects (NAS) which served as negative control for CSP-specific IgG subclasses. Although the NAS titre was lower than that of the malaria subjects in Nigeria, its IgG2 was, however, higher (0.16) than that of other subclasses. The mean absorbance values of total serum IgG subclass were higher than those of IgG subclasses specific to P. falciparum circumsporozoite antigen. The mean absorbance values of the total serum IgG subclass follows the order IgG2>IgG1>IgG4>IgG3. Interpretation & conclusion: Age and gender-dependent correlations of results suggest that acquired immunity could play a significant role in protection from malaria. Antibody levels are higher in male than female children of the same age group. Antibody levels also increase with age in both the male and female children.